ANCAMAN CYBERCRIME DI INDONESIA - Hapsari, Rian Dwi; Pambayun, Kuncoro Galih (Institut Pemerintahan Dalam Negeri, 2023)
Abstract The advancement of digital technology has significantly increased the threat of cybercrime, leading to issues such as identity theft, job loss, and disruptions to critical infrastructure. Meanwhile, cybercriminals continue to develop new techniques and strategies in committing their criminal acts. The purpose to describe the extent of cybercrime threats in Indonesia. This study employs a literature review method, which involves examining and analyzing literature related to cybercrime in Indonesia. The findings indicate that there has been an evolution in publications concerning cybercrime in Indonesia, shifting from an initial focus on understanding and regulations to a greater emphasis on technology, emerging threats, and their impact on various aspects of life and business. Common cyber threats in Indonesia include malware attacks, denial of service (DoS), distributed denial of service (DDoS), and phishing. These threats are often exacerbated by a lack of awareness and education about cybersecurity and limited enforcement of cybercrime laws. In conclusion, cybercrime threats in Indonesia are currently considered serious and highly dangerous due to their potential to create national issues. Efforts to address this issue should include strengthening law enforcement against cybercrime and enhancing public education on protecting oneself from online threats. Keywords: Cybercrime; Cybercrime Threats; Literature Review